Erratum to: Determination of the strong coupling constant αs(mZ) in next-to-next-to-leading order QCD using H1 jet cross section measurements - Andreev, Vladimir; Huber, Florian; Sauter, Michel David; Schöning, André (The European physical journal. C, Particles and fields, 2021)
The determination of the strong coupling constant αs(mZ) from H1 inclusive and dijet cross section data [1] exploits perturbative QCD predictions in next-to-next-to-leading order (NNLO) [2-4]. An implementation error in the NNLO predictions was found [4] which changes the numerical values of the predictions and the resulting values of the fits. Using the corrected NNLO predictions together with inclusive jet and dijet data, the strong coupling constant is determined to be αs(mZ) = 0.1166(19)exp, (24)th. Complementarily, αs(mZ) is determined together with parton distribution functions of the proton (PDFs) from jet and inclusive DIS data measured by the H1 experiment. The value αs(mZ) =0.1147,(25)tot obtained is consistent with the determination from jet data alone. Corrected figures and numerical results are provided and the discussion is adapted accordingly.
Im Titel sind "s" und "Z" tiefgestellt
Gesehen am 12.11.2021